DC‐TENGs: Direct Current Triboelectric Nanogenerators (Adv. Energy Mater. 45/2020). Issue 45 (1st December 2020) - Song, Yiding; Wang, Nan; Wang, Yuanhao; Zhang, Renyun; Olin, Håkan; Yang, Ya
Abstract : The latest advancements in direct current triboelectric nanogenerators (DC‐TENGs) are comprehensively summarized in article number 2002756 by Yuanhao Wang, Ya Yang and co‐workers. As an emerging member in the TENG family, DC‐TENGs can produce DC output and may find effective applications in energy storage or driving electronics. This overview of DC‐TENGs aims to attract increasing attention to the field and facilitate greater breakthroughs.